Cytotoxic Indole Diterpenoids from a Sphagneticola trilobata-Derived Fungus Aspergillus sp. PQJ-1 - Wenxing Li; Guohui Yi; Kaiwen Lin; Guangying Chen; Yang Hui; Wenhao Chen (Molecules, 2023)
Two new indole diterpene derivatives, 5S-hydroxy-β-aflatrem (1) and 14R-hydroxy-β-aflatrem (2), along with one known analogue, 14-(N,N-dimethl-L-valyloxy)paspalinine (3), were isolated from the fermentation broth of the fungus Aspergillus sp. PQJ-1 derived from Sphagneticola trilobata. The structures of the new compounds were elucidated from spectroscopic data and ECD spectroscopic analyses. All the compounds (1–3) were evaluated for their cytotoxicity against A549, Hela, Hep G2, and MCF-7 cell lines. Compounds 1 and 2 exhibited selective inhibition against Hela cells. Further studies showed that 1 significantly induced apoptosis and suppressed migration and invasion in Hela cells. Moreover, 1 could up-regulate pro-apoptotic genes BAX and Caspase-3 and down-regulate anti-apoptotic genes Bcl-xL and XIXP.